Staying together or breaking apart: Policy-makers' endogenous coalitions formation in the European Economic and Monetary Union - Giovanni Di Bartolomeo; Jacob Engwerda; Joseph Plasmans; Bas van Aarle (Fondazione Eni Enrico Mattei (FEEM), 2002)
In this paper, we analyze coordination of macroeconomic stabilization policies within the EMU by focusing, in a dynamic set-up, on asymmetries, externalities, and the existence of a multi-country context. We study how coalitions among fiscal and monetary authorities are formed and what are their effects on the stabilization of output and price. In particular, our attention is directed to study the consequences on these issues of different institutional contexts in which policy-makers may act. Among otherresults, we found that, in the presence of externalities, the occurrence of asymmetries is a necessary but not a sufficient condition for cooperation.
Keywords: C70; E17; E58; E61; E63; 330; Macroeconomic stabilization; EMU; coalition formation; Konjunkturpolitik; Internationale Wirtschaftspolitik; Eurozone; Geldpolitik; Finanzpolitik; Koalition; Spieltheorie